Proses Evolusi Inter-Organizational Relation (IOR) Pada Perusahaan Komponen Otomotif - Setiowiji Handoyo; Chichi Shintia Laksani (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2013)
Sustainability and improved performance of a company is closely associated with company's relationships with other organizations. Understanding the relationship between organizations (inter-organizational relations/IOR) is inseparable from the existence of a repeated process of interaction between or among organizations. In fact, the interaction process is related with time which determines whether a relationship increases from initial stage to mature stage. Through case studies, this study answers question of how the process of evolution IOR occur in automotive parts company with other organizations. This study also explains to what extent the strength evolution of the IOR process occurs, and the factors inducing IOR to reach the stage of mature/stable characterized by mutual trust. Results of the study showed that the evolutionary stage of IOR on automotive parts company with other actors vary widely. In the company forming a production network with principal, IOR has reached a mature stage. While the company which has no relationship with a production network with principals, trust in dealing with other actors (suppliers and principals) can be achieved with some length of time in interacting/dealing coupled in addition with an increase in the company's ability to meet the requirements from the principal/customer. Proponent factors for IOR until reaching a mature stage/stable in automotive component company is related with the company's position in the automotive business network, in addition to the ability of each party to honor the agreement that has been agreed in interacting.